Exploring Citizen Science for Sustainable Agricultural Extension Service Delivery in the Information Age (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Addressing challenges faced by the agricultural extension service delivery system and different needs of its relevant stakeholders in the 21st century information age require multi-dimensional innovative approaches and tools. This paper therefore, critically analyzes the relevancy of citizen science in agricultural extension service delivery, and suggests how advantages offered by the citizen science can be explored to sustainable delivery and agricultural extension service in the 21st century information age. A critical analysis method was used to systematically analyze concepts, texts, data, or phenomena to identify assumptions, determine meaning, and establish implications. The analysis observed that, the past growing relevance of citizen science as a technology-enhanced learning and its expanding scope is a good possibility worthy of being used to provide collective and a more comprehensive sustainable agricultural extension service in the 21st century information age. This would involve leveraging digital technologies to enable farmer-driven data collection, building community-based networks, and placing participatory research within formal extension systems to create inclusive, technology-mediated, and sustainable delivery of services.